1980
DOI: 10.1093/nar/8.22.5233
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical transformation of thymidine kinase (TK)-deficient mouse cells by herpes simplex virus type 1 DNA fragments purified from hybrid plasmids

Abstract: The thymidine kinase (TK) gene of HSV-1 has been cloned in Escherichia coli K12 plasmids, pMHl, pMHlA, and pMH4. These plasmids contain a 1,920bp HSV-1 TK DNA sequence, which replaces a 2,067 bp EcoR I to Pvu II sequence of plasmid pBR322 DNA. Superhelical DNAs of plasmids pMHl, pMHlA, and pMH4 as well as plasmid DNAs cleaved by EcoR I, Hinc II, Bgl II, Sma I, and Pvu II transformed TK-deficient LM(TK-) cells to the TKe phenotype. A 1,230bp EcoR ISma I fragment purified from pMHl DNA (and from plasmid pAGO DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1

Year Published

1981
1981
1984
1984

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
4
25
1
Order By: Relevance
“…We disagree with the implications from the work of Colbere-Garapin et al (1979) and more recently Kit et al (1980) that the Sinai site at 0.3045, and especially the 1.2 kb SmaI-EeoRI fragment, define the boundaries of the active HSV-1 TK gene. In our hands, when care was taken to ensure complete digestion, each of these enzymes reduced HSV-1 TK transfer at least 50-fold and in HSV-2 the EcoRI enzyme reduced the efficiency several thousand-fold.…”
Section: Dna)contrasting
confidence: 97%
“…We disagree with the implications from the work of Colbere-Garapin et al (1979) and more recently Kit et al (1980) that the Sinai site at 0.3045, and especially the 1.2 kb SmaI-EeoRI fragment, define the boundaries of the active HSV-1 TK gene. In our hands, when care was taken to ensure complete digestion, each of these enzymes reduced HSV-1 TK transfer at least 50-fold and in HSV-2 the EcoRI enzyme reduced the efficiency several thousand-fold.…”
Section: Dna)contrasting
confidence: 97%
“…Deletion of sequences within this stretch of 80 nucleotides results in decreased transcription of the tk gene in Xenopus oocytes (McKnight & Gavis, 1980) implying that this sequence is involved in gene recognition by RNA polymerase II. This is consistent with the inactivation of the HSV-1 tk gene by EcoRI cleavage (Wigler et al, 1977;Reyes et al, 1979), although Kit et al (1980) have reported successful transfection with sequences lacking this site.…”
Section: Discussionsupporting
confidence: 83%
“…Transformation of Ltk-cells to the TK+ phenotype with DNA of the cloned HSV-1 TK gene contained in recombinant plasmids or phage was performed under the same conditions as the phage-mediated gene transfer described above. Transformation efficiency comparable to that reported previously (12,38,40) could be attained by this method.…”
supporting
confidence: 89%
“…To establish a method for phage-mediated gene transfer, we used a model system of HSV-1 TK gene and Ltk-cells because this system has been well characterized and is easily available (4,12,25,36,40). We first constructed a recombinant phage carrying cloned HSV-1 TK gene, which also carries the minifibroin gene cloned in pBR322 (Tsujimoto, unpublished data) as a spacer to accommodate the packaging of phage particles (Fig.…”
Section: Resultsmentioning
confidence: 99%